Analisis Metode SMART Dalam Strategi Segmentasi Pasar (Studi Produk Tabungan Simitra Mikro di Bank Mitra Syariah Kantor Cabang Bojonegoro) - Agus Wahyu Irawan; Siti Lailatunnikmah Asfiah (Universitas Islam Darul 'ulum Lamongan, 2022)
This study aims to analyze the Smart Method on market segmentation strategies in increasing the number of simitra micro savings customers at Bank Mitra Syariah Bojonegoro Branch Office. Products owned by Bank Mitra Syariah include savings and financing products. One of the derivative products from savings products is the Simitra Micro Savings product. Simitra Micro Savings is a superior product owned by Sharia Partner Banks. The targets chosen by the Sharia Partner Bank are market traders. This research uses qualitative research and the analysis used is SMART analysis. This study uses data collection methods through interviews, observation, and documentation. Segmentation strategy is a method used by a company to divide the market into several different groups of buyers, which are seen from the point of view of the needs of traders. The segmentation strategy aims to make it easier for Micro Field Officers (PLM) in marketing products owned by Sharia Partner Banks, especially in simitra micro savings products. Simitra micro savings are savings or savings for small traders that are entrusted to the Sharia Mitra Bank which in the future can provide benefits to the merchant. Strategies implemented by sharia partner banks in marketing products owned by Sharia Partner Banks include dividing the market into several regions (segmentation), having the responsibility of officers in each region, determining targets for each region, offering superior products, establishing good relationships with customer.